The State, the self, and the willingness to co-exist: teachers’ perceptions of the other in Israel - Arafat, Malaka; Ramírez-García, Antonia; Maldonado, Miguel A.; Moyano, Manuel (Psychology, Society & Education, 2024)
As a result of structured separation in everyday life, Israel’s Arab and Jewish youth rarely interact, which contributes to a deepening and mutual sense of distance, distrust, and racism. Teachers, as agents of social change, can lead educational processes to bridge the ideological distance between Arabs and Jews in Israel, and to create an environment of dialogue and acceptance. This study used a sample of 300 teachers (150 from the Jewish ethnic group and 150 from the Arab ethnic group) to explore their perceptions and attitudes. Findings revealed that, compared to their Jewish counterparts, Arab teachers perceive the state’s attitude toward them as more negative. We found that Arab teachers’ perception of citizen-state relations was higher than that of Jewish teachers; identity perception among Arab teachers was lower than Jewish teachers; and coexistence perception among Jewish teachers was higher than Arab teachers. These findings can be a base for intervention programs at national and local levels and encourage the adoption of multicultural strategies to integrate Israel’s Arab population as equal citizens through social and political motivations.